The economics of the democratic deficit: The effect of IMF programs on inequality - Valentin Lang (The Review of International Organizations, 2020)
Does the International Monetary Fund (IMF) increase inequality? To answer this question, this article introduces a new empirical strategy for determining the effects of IMF programs that exploits the heterogeneous effect of IMF liquidity on loan allocation based on a difference-in-differences logic. The results show that IMF programs increase income inequality. An analysis of decile-specific income data shows that this effect is driven by absolute income losses for the poor and not by income gains for the rich. The effect persists for up to 5~years, and is stronger for IMF programs in democracies, and when policy conditions, particularly those that demand social-spending cuts and labor-market reforms, are more extensive. These results suggest that IMF programs can constrain government responsiveness to domestic distributional preferences.
Keywords: F53; O19; 320; International Monetary Fund (IMF); Inequality